Topoisomerase I Inhibitory Activity and 3D QSAR Studies of Chromone Derivatives - Chirattikan Maicheen (Science Faculty of Chiang Mai University, 2019)
Topoisomerase I (Top I) is the molecular target for a diverse set of anticancer agents. This study was a continuation of previous work examining the Top I inhibitory activity of a series of chromone derivatives. Nine chromones were evaluated using eukaryotic DNA TOP I drug screening kit. The most potent inhibitor, chromone 20 showed greater inhibitory activity (IC50 = 0.83 mM) than the previously reported chromone compounds as well as the known Top I inhibitor, camptothecin. To develop the structure-Top I inhibitory activity relationship, the 3 dimensional quantitative structure-activity relationship (3D QSAR) were performed using comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA). The best CoMFA model gave cross-validated r2 (q2) = 0.578 and non cross-validated r2 = 0.995 while CoMSIA gave q2 = 0.632, r2 = 0.996. The contour maps provide the fruitful structural features which are useful for designing new compounds with higher activity.